Family Social Support Module for Stroke Patients with Attention to Local Wisdom in Malang - Moh. Zainol Rachman (Health Notions, 2020)
Indonesia is currently experiencing changes in the epidemiology of non-communicable diseases where stroke has undergone a demographic and technological transition, causing the age prevalence of stroke sufferers that previously suffered by people aged > 50 years now shifted to a young age. Increasing the available social support can be an important strategy in reducing or preventing mental distress and warding off post-stroke depression. The role of family and people around them to provide life support for stroke sufferers will be very meaningful. The purpose of this study was to describe the attractiveness of the Family Social Support Module for Stroke Patients with Attention to Local Wisdom in Malang. This study used a research and development method with a longitudinal research design. The results of this study were that the modules compiled by the researchers succeeded in changing family behavior in the social support of stroke sufferers and most of them stated that the module was good. Social support, especially from family, plays an active role in the patient's recovery. Family social support must be maintained properly, this will help stroke patients carry out activities independently and get strong family reasons as a supporting factor for the patient's recovery. Keywords: stroke sufferer; module; family social support